การบำบัดน้ำเสียจากอุตสาหกรรมสิ่งทอโดยกระบวนการอิเล็กโตรเฟนตอน - มารุต โปราณานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
Wastewater from textile industry was consisted of large quantity of oil and grease. In this work, the treatment of wastewater from textile industry by using the electrofenton has been studies. This study was divide in two parts. The first part was the wastewater treatment in bacth process. The studied parameters in this part were initial concentration of oil and grease, current density, circulating flowrate, and concentration of hydrogen peroxide. The optimum condition in batch process was found at initial concentration of oil and grease 450 micrograms/litre, current density of 22 A/m[superscript 2], circulating flowrate of 6 l/min, and concentration of hydrogen peroxide of 0.5 M. According to this condition the removal efficiency of oil and grease in the range of 150-450 micrograms/litre was similar. The removal percentages of oil and grease, COD, and BOD in 45 minute were obtained 93.9%, 89.2%, and 88.9% respectively. The second part was the wastewater treatment with electrofenton in continuous process. The studied parameters in this part were flowrate of wastewater, mode of hydrogen peroxide feed, and feed rate of hydrogen peroxide. The results indicated that the optimum condition in continuous process found at the flowrate of 0.1 l/min by using 0.5 M H[subscript 2]O[subscript 2] in pulse feed with feed rate of 2 millilitre/min. Approximately 92.5%, 79.6% and 69.8% of oil and grease, COD, and BOD were respectively removed within 60 minute.